Diagnostic Accuracy of Sentinel Lymph Node Biopsy with Methylene Blue for Detection of Sentinel Lymph Node Metastasis Taking Histopathology as Gold Standard - Gul Rukh Khawar, Muhammad Azam Tayyab, Saad Arshad, Uzair Ahmed Qureshi, Abdur Rehman Alvi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study was to determine the diagnostic accuracy of sentinel lymph node biopsy using methylene blue for diagnosis of sentinel lymph node metastasis taking histopathology as a reference standard. Material and Methods: The cross-sectional study was conducted at the Surgery Department, DHQ Hospital, Gujranwala. 126 patients accomplishing the inclusion criteria were included in this research. The procedure was carried out under general anesthesia. After draping, 5ml injection of 1% methylene blue was administered in the subareolar area, divided in 3 injections. Massage was done for 10–15 min. A valuable anatomical landmark was made to perform the incision 1cm beneath the axillary hairline. Dissection of skin and subcutaneous tissue was made followed by the dissection of the clavipectoral fascia to invade the axilla, and lymphatics having blue staining were recognized. Sensitivity, specificity, PPV, NPV, and diagnostic accuracy of SLNB was calculated using 2×2 table, considering histopathology as a reference frame. Results: Mean age of the study participants was 54.02 ± 12.07 years with minimum age as 25 years and maximum age as 75 years. There were 59(46.8%) females who were diagnosed of sentinel lymph node with methylene blue and 58(46%) females were positive with Sentinel lymph with histopathology. The sensitivity, specificity, positive predictive value, negative predictive value and overall diagnostic accuracy of methylene blue was 89.66%, 89.71%, 88.14%, 91.04% and 89.68% respectively. Stratification of data was done for age groups, duration of disease, marital status, parity, and type of treatment and high sensitivity, specificity, PPV, NPV, and diagnostic accuracy was found in each strata with significant p-value <0.001. Conclusion: It is concluded that on the basis of results of current study the sensitivity, specificity, PPV, NPV, and overall diagnostic accuracy of methylene blue was highly significant in assessing sentinel lymph nodes. Hence, we can implement the results of this study for our population and implement the utilization of SLNB method making use of methylene blue dye instead of going for the excision biopsy. It poses fewer complications as compared to other comparable procedures. Also, it is an accurate, easily accessible and cheap method to evaluate the status of metastasis of lymph nodes in the axilla.